Study of antioxidant capacity and metabolization of quebracho and chestnut tannins through in vitro gastrointestinal digestion-fermentation. (October 2018) - Molino, Silvia; Fernández-Miyakawa, Mariano; Giovando, Samuele; Rufián-Henares, José Ángel
Graphical abstract: Highlights: Quebracho and chestnut wood extracts are natural rich sources of tannins. FRAP and ABTS methods revealed tannins extracts as effective antioxidant agents. The release of short chain fatty acids suggested a high prebiotic potential. A first attempt to study the metabolism of tannin extracts was realised. Abstract: Quebracho (QUE) and chestnut (CHE) are natural sources of tannins, but there are no connection between QUE, CHE and human health. The study investigated the antioxidant response and metabolization of tannin extracts trough in vitro digestion-fermentation. The FRAP assay pointed a higher reducing capacity of CHE than QUE (6.90 vs. 5.07 mmol Trolox/g), in contrast to a stronger scavenging activity of QUE (8.16 mmol Trolox/g vs 6.70 mmol Trolox/g). The results obtained showed a decrease of the antioxidant capacity of tannins after microbial fermentation, but a high prebiotic activity through release of short-chain fatty acids of both CHE (11.14 mmol/g) and QUE (4.79 mmol/g) was observed. The UPLC-MS investigations on digested and fermented tannins gave an identification and semi-quantification of 18 compounds, including hydrolysable and condensed tannins and their metabolites. The results represent a valid basis for further studies on the potential use of these wood extracts in human diet.